Analisis Strategi Produksi dan Pemasaran Benih Kelapa Sawit (Elaeis guineensis Jacq) pada PT Socfin Indonesia - Zulkifli Zulkifli; Syahbudin Hasibuan; Ihsan Effendi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Global demand for vegetable oil, especially palm oil has increased the need for certified oil palm germinated seeds. This study analyzes internal and external factors influencing the production and marketing of germinated seeds at PT Socfin Indonesia and formulates competitiveness strategies for domestic and export markets. The research was conducted at PT Socfin Indonesia, March–July 2026, using interviews, field observations, questionnaires, and secondary data; analyses used SWOT, IFE, and EFE. Key strengths: reputation and experience, superior DxP varieties, quality standards and certification, integrated digital data management, and international networks. Weaknesses: centralized distribution, limited promotion, premium pricing. Opportunities: export markets, government programs (including PSR), strong global CPO demand. Threats: intense price competition, risk of quality decline, negative campaigns. Strategies: leverage product quality, certification, and digital traceability; expand digital promotion/distribution; strengthen end-to-end quality control and sustainability communication.